Managing Mexico : economists from nationalism to neoliberalism - Babb, Sarah L. (Princeton University Press, 2001)
Just one generation ago, lawyers dominated Mexico's political elite, and Mexican economists were a relatively powerless group of mostly leftist nationalists. Today, in contrast, the country is famous, or perhaps infamous, for being run by American-trained neoclassical economists. In 1993, the Economist suggested that Mexico had the most economically literate government in the world--a trend that has continued since Mexico's transition to multi-party democracy. To the accompanying fanfare of U.S. politicians and foreign investors, these technocrats embarked on the ambitious program of privatization, deregulation, budget-cutting, and opening to free trade--all in keeping with the prescriptions of mainstream American economics. This book chronicles the evolution of economic expertise in Mexico over the course of the twentieth century, showing how internationally credentialed experts came to set the agenda for the Mexican economics profession and to dominate Mexican economic policymaking. It also reveals how the familiar language of Mexico's new experts overlays a professional structure that is still alien to most American economists. Sarah Babb mines diverse sources--including Mexican undergraduate theses, historical documents, and personal interviews--to address issues relevant not only to Latin American studies, but also to the sociology of professions, political sociology, economic sociology, and neoinstitutionalist sociology. She demonstrates with skill how peculiarly national circumstances shape what economic experts think and do. At the same time, Babb shows how globalization can erode national systems of economic expertise in developing countries, creating a new class of ''global experts.''